Group foraging dynamics in mice: unraveling the link between neural activity and the emergence of workers and freeriders - Lee, Jaehyun; Lee, Gyu-Hwan; Kim, Seoyoung; Jung, Dayoung; Kim, Jaehoon; Choi, Ji Hyun (Neuroscience 2024, 2024)
From the perspective of collective action theory, achieving the common good requires individual contributions to group welfare. However, the challenge of free-riders, who benefit without contributing, complicates the balance between effort and resource sharing. While previous studies have examined group characteristics and voluntary participation affecting free-riding, less is known about the intrinsic decision-making processes behind the emergence of participants and free-riders. To explore these dynamics, we conducted a 'risk-taking food retrieval' experiment with mice. Mice cohabitated with a spider robot in an arena and had to retrieve shared food placed on the robot. Using CBRAIN, we tracked neural activity in the mPFC, NAc, and BLA―regions associated with decision-making, reward, and fear.